Radiographic and echocardiographic evaluation in rescued Korean raccoon dogs (Nyctereutes procyonoides koreensis) - Park, Junu; Kim, Myeongsu; Han, Jae-Ik; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2024)
Introduction: Nyctereutes procyonoides koreensis (Korean raccoon dog), a member of the Canidae family, is anatomically similar to dogs. Previous studies have used vertebral heart scale measurements to measure the cardiac size of Korean raccoon dogs on thoracic radiographs; however, the use of additional cardiac size indices, such as vertebral left arial score, intercostal space, cardiothoracic ratio, and echocardiographic indices, has not been reported. Therefore, this study aimed to establish normal reference ranges for various thoracic radiographic and echocardiographic indices in normal Korean raccoon dogs. Methods: Twenty-six Korean raccoon dogs (eleven males and fifteen females) were included in this study. The thoracic radiographic indices, vertebral heart scale score, and vertebral left atrial score were measured in the vew. The intercostal space and cardiothoracic ratio were measured in the ventrodorsal view. The echocardiograms were evaluated in the right parasternal long and short axis view and left parasternal apical view. Results: The mean values for the thoracic radiographic and echocardiographic indices were as follows: vertebral heart scale, 9.12±0.74; vertebral left atrial score, 1.5 ± 0.31; intercostal spaces, 3.17 ± 0.34; cardiothoracic ratio, 0.69 ± 0.07; left atrial to aortic root ratio, 1.22 ± 0.14; main pulmonary artery to aorta ratio, 1.22 ± 0.14; left ventricular end-diastolic internal diameter normalized for body weight, 1.36 ± 0.19; end-diastolic volume index, 51.07 ± 19.6; end-systolic volume index, 16.54 ± 7.45; the peak velocity of early diastolic transmitral flow, 73.13 ± 15.46 cm/s; and the ratio between the transmitral flow velocities and the peak early diastolic velocity, 1.77 ± 0.47. Only percent increase in the left ventricular end-systolic internal diameter was negatively correlated with body weight. The remaining indices showed no correlations with body weight. Conclusions: To the best of our knowledge, this is the first case report covering both thoracic radiographic and endocardiographic indices for Korean raccoon dogs. Thus, the thoracic radiographic and echocardiographic indices established in this study may be used to evaluate the cardiac condition of Korean raccoon dogs.